Rozwiąż równania:
1) (3x-4) do potegi 2 +4(2x+1) do potęgi 2 = (5x+2)(5x-2)

2) 1-4(x+2) do potęgi 2 = (1-2x)(1+2x)

3) (3-2x) do potęgi 2 +(x+4)(x-3) = 5(x-2) do potęgi 2 +7

4) 2(x-0,2) do potęgi 2 = x do potegi 2 +(x+0,1) do potegi 2

2

Odpowiedzi

2009-12-14T17:29:37+01:00
1) (3x-4) do potegi 2 +4(2x+1) do potęgi 2 = (5x+2)(5x-2)
9x²-24x+16+2+4(4x²+4x+1)=25x²-4
9x²-24x+16+2+16x²+16x+4=25x²-4
9x²-24x+16x²+16x-25x²=-4-16-2-4
-8x=-26 /:(-8)
x=3,25

2) 1-4(x+2) do potęgi 2 = (1-2x)(1+2x)
1-4(x²+4x+4)=1-4x²
1-4x²-16x-16=1-4x²
-4x²-16x+4x²=1-1+16
-16x=16 /:(-16)
x=-1

3) (3-2x) do potęgi 2 +(x+4)(x-3) = 5(x-2) do potęgi 2 +7
9-12x+4x²+x²-12=5(x²-4x+4)+7
9-12x+4x²+x²-12=5x²-20x+20+7
-12x+4x²+x²-5x²+20x=20+7-9+12
-12x=30 /:(-12)
x=-2,5


4) 2(x-0,2) do potęgi 2 = x do potegi 2 +(x+0,1) do potegi 2
2(x²-0,4x+0,04)=x²+x²+0,2x+0,01
2x²-0,8x+0,08=x²+x²+0,2x+0,01
2x²-0,8x-x²-x²-0,2x=0,01-0,08
-x=-0,07 I*(-1)
x=0,07

2009-12-14T18:10:23+01:00
1.)(3x-4)²+4(2x+1)²=(5x+2)(5x-2)
9x²-24+16+4(4x²+4x+1)=25x²-10x+10x-4
9x²-24x+16x²+16x+4=25x²-4
25x²-8x+20=25x²-4
-8x=-16 /:-8
x=2

2.)1-4(x+2)²=(1-2x)(1+2x)
1-4(x²+4x+4)=1+2x-2x-4x²
1-4x²-16x-16=1-4x²
-16x-15=1
-16x=1+15
-16x=16
x=-1

3.) (3-2x)² +(x+4)(x-3) = 5(x-2)²+7
9-12x+4x²+x²-12=5(x²-4x+4)+7
9-12x+4x²+x²-12=5x²-20x+20+7
-12x+4x²+x²-5x²+20x=20+7-9+12
-12x=30 /:(-12)
x=-2,5

4.)2(x-0,2)²=x²+(x+0,1)²
2(x²-0,4x+0,04)=x²+x²+0,2x+0,01
2x²-0,8x+0,08=2x²+0,2x+0,01
-0,8x-0,2x=0,01-0,08
-x=-0,07
x=0,07